Conflicts dynamics in democratic and autocratic regimes, 1946-2008 - Panel, Sophie (2017)
The aim of this thesis is to analyze the impact of political regime type on the onset of violent conflicts. Using statistical analysis on a dataset that covers the period from 1946 to 2008, I investigate the effects of regime type on civil war, military coups, physical integrity rights violations, and the initiation of militarized interstate disputes. What foremost predicts instances of violent conflict is the extent to which regimes rely on binding, predictable rules regarding the selection of the chief executive: thus, I find that monarchies and democracies are more stable and peaceful than any other regime. Among regimes that lack such rules, I find that military dictatorships experience coups more frequently than party regimes, but this is the only outcome that can be clearly attributed to authoritarian regime type: other observed differences either stem from the mutual relationships between different manifestations of political violence, or from the security environment in which such regimes emerge. To sum up, was seems to explain political regimes’ propensity to experience or use violence is the extent to which they are institutionalized, and the extent to which leaders are secure in office.
Keywords: Hochschulschrift; Geschichte 1946-2008; Konflikt; Autokratie; Demokratie